Effect of antihypertensive drugs treatment on oxidative stress in heart of N-nitro-L-arginine methyl ester (L-Name) administered spontaneously hypertensive rat - Nik Yusoff, Nik Syamimi (2015)
Hypertension is a major risk factor contributing to cardiovascular, cerebrovascular and renal diseases. The pathogenesis of essential hypertension is multifactorial and highly complex. An imbalance in the oxidant/antioxidant status has been proposed as an important pathogenic mechanism in hypertension as well as hypertension induced organ damage including heart. As hypertension contributes to organ damage, antihypertensive drug treatment aims to reduce not only the blood pressure but also hypertension induced organ damage. However, the effect of antihypertensive drugs α2-adrenergic agonist (Clonidine) and Angiotensin-Converting Enzyme (ACE) inhibitor (Enalapril) on oxidative stress in heart has not been well studied. Therefore, this study investigate the effect of Clonidine and Enalapril on oxidative stress markers, enzymatic /non-enzymatic antioxidants and nitric oxide (NO) in heart of spontaneously hypertensive rat (SHR) and SHR administered NO synthase inhibitor, N-nitro-L-arginine methyl ester (SHR+L-NAME). In the first phase of study, the comparison of levels of oxidative stress markers and antioxidant defence system in normotensive Wistar Kyoto Rats (WKY) and SHR, as well as WKY+L-NAME and SHR+L-NAME was carried out. SHR developed hypertension by 8 weeks accompanied by increased in oxidative status markers TBARS and PCO levels, increased CAT, GR and GST activities, reduced GPx activity, enhanced GSH and GSSG level, reduced GSH : GSSG ratio, NO level in heart. In WKY+L-NAME, the inhibition of NO synthase by L-NAME successfully developed hypertension by weeks 20 onwards. In this model there is an increased TBARS and PCO level, reduced GPx activity, enhanced GR and GST activities, increased GSSG level and reduced NO bioavailability. In SHR+L-NAME, the systolic blood pressure values exceed >200 mmHg, exhibit severe hypertensive condition. SHR+L-NAME showed an increased TBARS and PCO level, enhanced GR and GST activity, reduced GPx activity, increased GSSG and reduced NO level compared to SHR . In the second phase of study, the effect of Clonidine treatment on oxidant/antioxidant status in heart of SHR and SHR+L-NAME was assessed. Clonidine treatment reduced the SBP and increased the TAS level in SHR and SHR+LNAME, reduced TBARS in SHR+L-NAME, reduced PCO level, GST activity and enhanced the level of GSH and GSH:GSSG ratio and CAT activity in SHR and SHR+L-NAME, reduced GSSG level in SHR+L-NAME, as well as increased NO level in SHR. In the third phase of study, the effect of Enalapril treatment on oxidant/antioxidant status in heart of SHR and SHR+L-NAME was assessed. It reduced the level of SBP, TBARS, PCO, GR and GST activities and increased the level of TAS, GSH, GSH:GSSG ratio and CAT activity in SHR and SHR+L-NAME, enhanced SOD activity in SHR, and reduced GSSG level in SHR+L-NAME. In conclusion, this study suggested that the oxidative stress play a role in the development and/or maintenance of hypertension and the imbalance in oxidant/antioxidant status in heart might leads to its damage in hypertensive rats. Antihypertensive drugs treatment such as Clonidine and Enalapril ameliorate the oxidative stress in heart of hypertensive rats and thereby these drugs might prevent its damage in addition to their role in reducing blood pressure.